Effects of antibrowning agents on the quality of mango fruit roll - Morano, Rosevic Montaje (2000.)
The study involved improvement of the mango fruit roll's sensorial, physico-chemical and microbial properties.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Mango; Rolls; Mango fruit roll